2020
DOI: 10.3389/fnhum.2020.00350
|View full text |Cite
|
Sign up to set email alerts
|

Links Between the Neurobiology of Oxytocin and Human Musicality

Abstract: The human species possesses two complementary, yet distinct, universal communication systems—language and music. Functional imaging studies have revealed that some core elements of these two systems are processed in closely related brain regions, but there are also clear differences in brain circuitry that likely underlie differences in functionality. Music affects many aspects of human behavior, especially in encouraging prosocial interactions and promoting trust and cooperation within groups of culturally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 337 publications
(567 reference statements)
1
51
0
7
Order By: Relevance
“…Interpersonal coordination has been evolutionarily selected for its important role in social cohesion or bonding (Chartrand and Lakin, 2013 ); these behaviors help connect the self to others, and recent studies have shown that they drive neural coupling (Bernieri and Rosenthal, 1991 ; Hasson et al, 2012 ; Hasson and Frith, 2016 ). Other theories on the evolution of dance and other creative art forms exist but are beyond the scope of this review (Morriss-Kay, 2010 ; Sigaki et al, 2018 ; Zaidel, 2018 , 2020 ; Savage, 2019 ; Harvey, 2020 ). In this section, we discuss the evolutionary advantages of interpersonal coordination, and by viewing dance through this lens, we see that dance is a complex physical activity that involves mimicry and synchrony in a variety of neurobehaviors.…”
Section: Evolutionary Purpose Of Dance: Driving Interpersonal Coordinmentioning
confidence: 99%
“…Interpersonal coordination has been evolutionarily selected for its important role in social cohesion or bonding (Chartrand and Lakin, 2013 ); these behaviors help connect the self to others, and recent studies have shown that they drive neural coupling (Bernieri and Rosenthal, 1991 ; Hasson et al, 2012 ; Hasson and Frith, 2016 ). Other theories on the evolution of dance and other creative art forms exist but are beyond the scope of this review (Morriss-Kay, 2010 ; Sigaki et al, 2018 ; Zaidel, 2018 , 2020 ; Savage, 2019 ; Harvey, 2020 ). In this section, we discuss the evolutionary advantages of interpersonal coordination, and by viewing dance through this lens, we see that dance is a complex physical activity that involves mimicry and synchrony in a variety of neurobehaviors.…”
Section: Evolutionary Purpose Of Dance: Driving Interpersonal Coordinmentioning
confidence: 99%
“…Such applications/extensions include: clinical applications in patients with amnesia/Alzheimer's disease ( del Mastrao et al ) and neurodevelopmental disorders ( Kasdan et al ); applications to music education ( Morrison ) and sleep research ( Akkermann et al); proposing additional behavioral experiments to explore relationships between specific musical features and specific psychological mechanisms ( Sachs et al ); proposing additional cultural transmission experiments to explore mechanisms of cultural evolution ( Lumaca et al; Scott-Philipps et al ); theoretical extension to the evolution of dance ( Brown ), gesture ( Gardiner ), play ( Ashley ), and story-telling ( Trevor & Frühholz) ; exploring coevolution of music and language ( Benítez-Burraco ); incorporation of the role of knowledge songs ( Levitin ); cross-cultural extensions to Chinese music ( Wang & Zou ); capturing variation in musicality at the levels of development ( Hannon et al ), vocal production ( Pfordresher ), and genomes ( Tichko et al ); and further details of neurobiological mechanisms including the roles of ventromedial prefrontal cortex ( Belfi ), the cerebellum ( Fritz ), oxytocin ( Hansen & Keller ; cf. Harvey, 2020), entrainment ( Grahn et al ), and emotion ( Gingras; Juslin ). We do not have space to address each of these proposals in detail, but we are delighted our proposals have stimulated such productive extensions and we look forward to seeing the results of their proposals.…”
Section: Tests Extensions and Applicationsmentioning
confidence: 99%
“…In healthy young women, relaxing music reduced stress levels much faster than silence, while the opposite was detected for rap music [67]. Moreover, listening to classical music in musically experienced participants resulted in the differential expression of genes related to dopamine release and signaling, synaptic function, cognition, neurogenesis, long-term potentiation, dephosphorylation, ATP synthase-coupled proton transport, cytolysis, and positive regulation of caspase, peptidase, and endopeptidase activities [68]. While there was a clear trend showing increased peripheral oxytocin and decreased cortisol levels in participants actively engaged in music performance (reviewed in [69]), more research is needed to reveal the effects induced by different music forms, ie, familiar vs. non-familiar, public vs. private performance, or arousing vs. relaxing music.…”
Section: Music Therapy (Mt)mentioning
confidence: 98%